Pertanggungjawaban Brand Ambassador atas Wanprestasi PT. Dana Syariah Indonesia Ditinjau dari Konsep Ajīr Khāṣṣ Wahbah Zuhaili - Raudhtul Jannah; Mustapa Khamal Rokhan (Aksioreligia, 2026)
The use of brand ambassadors in digital marketing raises legal issues when the promoted company commits a breach of contract, resulting in losses for investors. This study aims to analyze the limits of a brand ambassador's liability regarding PT. Dana Syariah Indonesia's breach of contract, based on Indonesian positive law and the concept of ajīr khāṣṣ (specific employee/contractor) according to Wahbah Zuhaili. This is an empirical/sociological legal study employing both conceptual and case-based approaches. The case approach involves examining the legal facts of the PT. Dana Syariah Indonesia breach-of-contract case, subsequently analyzing them against positive legal provisions and the legal thought of Wahbah Zuhaili. The findings indicate that a brand ambassador holds the status of ajīr khāṣṣ within an ijārah (service contract) arrangement characterized by yad amānah (trust-based possession); consequently, they do not bear the company's business risks. This principle aligns with Surah Al-Mā'idah, Verse 1, which emphasizes the obligation to fulfill contractual agreements. Therefore, a brand ambassador bears no financial liability (ḍamān) for the company's breach of contract, provided they have conducted due diligence and are not proven to have committed ta‘addī (transgression) or taqṣīr (negligence). Legal liability remains with the company, as the party obligated to fulfill the contractual performance owed to investors.